2021
DOI: 10.1080/15435075.2021.1930005
|View full text |Cite
|
Sign up to set email alerts
|

The role of hydropower in renewable energy sector toward co2 emission reduction during the COVID-19 pandemic

Abstract: Due to the Coronavirus 2019 (COVID-19) pandemic social distance became a necessary strategy adopted in order to curb the fast-rise of infection. However, this strategy adopted by the government has impacted the socio-economic activities and lives of citizens as such new adaptive measures had to be put in place to cope with the pandemic. Accordingly, this study explores the relationship between the current COVID-19 pandemic on hydropower and energy sector in relation to Carbon dioxide (CO 2 ) emission reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…A smooth transition to renewable energy technologies via bioenergy with carbon capture and storage along with atmospheric carbon capture can also be a fascinating strategy for moving towards energy efficiency (Budinis, 2020;Ope Olabiwonnu et al, 2021). Other than this, hydrogen economy is another promising approach for low carbon energy system since hydrogen is a versatile carbon-free energy carrier and can support energy service across various energy sectors (Grigoriev et al, 2020;Thomas et al, 2020).…”
Section: Recovery Plan and Sustainabilitymentioning
confidence: 99%
“…A smooth transition to renewable energy technologies via bioenergy with carbon capture and storage along with atmospheric carbon capture can also be a fascinating strategy for moving towards energy efficiency (Budinis, 2020;Ope Olabiwonnu et al, 2021). Other than this, hydrogen economy is another promising approach for low carbon energy system since hydrogen is a versatile carbon-free energy carrier and can support energy service across various energy sectors (Grigoriev et al, 2020;Thomas et al, 2020).…”
Section: Recovery Plan and Sustainabilitymentioning
confidence: 99%
“…Furthermore, Ummalla and Samal (2018) results indicate a bidirectional causality among economic growth, CO 2 emissions and hydropower energy utilization, and a unidirectional causality running from hydropower energy utilization to economic growth. Moreover, Ope Olabiwonnu et al (2022) outcomes display that impact of Coronavirus (COVID-19) on energy and hydropower with environmental degradation decreased during the pandemic. Additionally, Murshed et al (2021) empirically found that utilization of coal and oils upsurges environmental degradation while higher utilization of natural gas and hydropower energy utilization is seen to decrease environmental pollution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study evaluated mixtures of non-renewable and renewable fuels in terms of their degrees of pollution damage; this has generally not been explored in the past. The earlier literature is mainly limited to the use of nuclear energy [33][34][35], biomass fuel [36,37], solar energy [38,39], wind energy [40,41], hydropower [42,43], and geothermal energy [44,45] sources in different economic settings. In comparison, the literature has largely overlooked the use of coal and brown coal and refined oil in the global data set, which is essential for formulating a sustainable policy agenda.…”
Section: Hypotheses 3 (H3) the Production Of Refined Oil Will Likely ...mentioning
confidence: 99%